CEiA_07:08:2019.xlsx - Golicz, Karolina K.; Hallett, Stephen H.; Sakrabani, Ruben; Ghosh, Joy (Cranfield University, 2020)
Data collected during laboratory experiments, which took place at Cranfield University. The dataset provides raw data, which accompanies a scientific paper titled: 'Development of a smartphone-mediated screening tool for determining soil nutrient content analysis in Indonesia'.
Keywords: Smartphone apps'; 'soil sciences'; 'Agronomy & Agriculture'; 'Agronomy'; 'Farm Management; Rural Management and Agribusiness'; 'Sustainable Agricultural Development'; 'Soil Science'